The crime of doing medical work without a license (A comparative study) - Amer Mahmoud, Lama (International Journal of Psychosocial Rehabilitation, 2020)
Medical work is considered one of the most important works that can undermine the human right to the safety of his body, so legislations, including the legislation in question, have sought to regulate the practice of this work, and to establish the rules and legal frameworks that govern it, in a way that removes the criminal character and gives it the character of legitimacy, And it shall exempt the person responsible from any criminal liability. In view of the seriousness involved in the practice of medical work on the right to body safety, the legislation subject to comparison stipulated that the medical practitioner must possess the scientific qualifications that would enable him to do this work, and that he possesses the necessary legal license, otherwise it will cease to be medical work Legitimate and becomes an illegal activity, the person in charge is asked about a crime, we called it the crime of practicing medical work without a license, and it is one of the serious crimes that has its implications, and its punishment is in accordance with the principle of legality.